2011
DOI: 10.5703/1288284314258
|View full text |Cite
|
Sign up to set email alerts
|

Indiana Pavement Preservation Program

Abstract: State highway agencies are facing immense pressure to maintain roads at acceptable levels amidst the challenging financial and economic situations. In recent years, pavement preservation has been sought as a potential alternative for managing the pavement assets, believing that it could provide a cost-effective solution in maintaining infrastructural conditions and meeting user expectations.While the concept of pavement preservation is has been established at the project level, there is still a significant gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
(32 reference statements)
2
21
0
Order By: Relevance
“…INDOT also developed short and long term performance models for the following pavement preservation treatments: crack seal, patching, microsurfacing and thin overlay. These can be found in Ong et al (2010). Chan et al (2010) list the following expected pavement extension lives for pavement preservation treatments in Ontario: crack sealing = 3 years, slurry seal = 3 to 5 years, microsurfacing = 7 to 9 years, chip seal = 4 to 6 years, hot in-place recycling (HIR; heated surface is milled down to 40 -50 mm, scarified material is rejuvenated and reprofiled) = 10 to 12 years similar to an HMA overlay.…”
Section: Expected Life Of Treatmentsmentioning
confidence: 96%
See 1 more Smart Citation
“…INDOT also developed short and long term performance models for the following pavement preservation treatments: crack seal, patching, microsurfacing and thin overlay. These can be found in Ong et al (2010). Chan et al (2010) list the following expected pavement extension lives for pavement preservation treatments in Ontario: crack sealing = 3 years, slurry seal = 3 to 5 years, microsurfacing = 7 to 9 years, chip seal = 4 to 6 years, hot in-place recycling (HIR; heated surface is milled down to 40 -50 mm, scarified material is rejuvenated and reprofiled) = 10 to 12 years similar to an HMA overlay.…”
Section: Expected Life Of Treatmentsmentioning
confidence: 96%
“…Service life and cost of treatments in Ontario (adapted from Wei and Tighe 2004)Ong et al (2010) have developed long term pavement performance models for existing pavements as part of INDOT's pavement preservation program. The models for flexible pavements were developed for functional performance indicators such as pavement roughness and rut depth using regression analysis.…”
mentioning
confidence: 99%
“…Also, Ong et al (2010) evaluated short-and long-term effectiveness of pavement preservation treatments in Indiana using the pavement condition data, traffic data, and work information from the Indiana pavement management system. From the study, it was found that crack sealing provided no significant improvement in International Roughness Index (IRI) of pavements (Ong et al, 2010). However, more recent study from Lu and Tolliver (2012) on short-term effectiveness of pavement treatment in IRI, based on LTPP data, reported that crack sealing application offered a significant pavement performance jump in terms of IRI down to 28 in./mile.…”
Section: Effectiveness Of Sealing/fillingmentioning
confidence: 97%
“…Another study conducted with Long-Term Pavement Performance (LTPP) data in 2012 on the short-term effectiveness of pavement treatment on the International Roughness Index (IRI) reported that crack sealing application offered a significant jump in pavement performance in terms of IRI down to 28 in./mile (Lu & Tolliver, 2012). However, two Indiana studies found that there were no significant IRI differences between sealed and non-sealed pavements (Fang, Galal, Ward, & Haddock, 2003) and prior to and after the sealing application (Ong, Nantung, & Sinha, 2010). For the effectiveness of routing in crack sealing practice, Masson (1997) found that routing on an asphalt concrete pavement created micro-cracks at the bitumen aggregate interface and within aggregates.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The review of the past literature reveals that pavement deterioration is significantly influenced by climatic and traffic load (see [8] - [15]). Nevertheless, the problem would arise when trying to replicate the fluctuation of these two pavement deterioration factors.…”
Section: Literature Reviewmentioning
confidence: 99%